Geplante Obsoleszenz Hinter den Kulissen der Produktentwicklung - Poppe, Erik; Longmuß, Jörg (Forschung aus der Hans-Böckler-Stiftung, 2019)
Time and again one reads that manufacturers deliberately design their products in such a way that they break prematurely. The victims: the customers. Many manufacturers, however, want to delay the wear. How do you go about planning for obsolescence? The book presents for the first time the view and experiences of those who develop, design and manufacture products. The contributions deal with reparability as a business model, product lifecycle management, obsolescence as a management topic, the role of state influence and the social drivers of the short-lived consumer goods.